PENGUJIAN AKTIVITAS LIPASE YANG DIHASILKAN OLEH BACILLUS MEGATERIUM TERHADAP MINYAK KENARI MENGGUNAKAN SEDIAAN TABLET ENZIM LIPASE SEBAGAI PEMBANDING AKTIVITASNYA - Kiehiunglie, Nicholas
Oils are often used as the ingredient for the production of pharmaceutical preparations. Lipase roles in industrial production includes the modification of oils , for examples the melting point, boiling point, and etc. This research aimed to determined the unknown activities of lipase content in Bacillus megaterium growth medium by comparing it to the activities of lipase tablet which available commercially. The reference enzyme are obtained by dissolving commercial enzyme tablet into 0.9% NaCl solution and sample enzyme from the growth medium of Bacillus megaterium after 1 day in which both of them are centrifuged and the supernatant solution are taken. The effect of each enzyme are assayed by incubate the supernatant to the Canarium oil, and then saponificated and derivated so it can be analyzed by using HPLC. Canarium oil which are not incubated with enzyme are saponificated, derivated and analyzed with the same methods. According to the experiment result, the fatty acid that shows decent linearity from the increased concentration of enzyme table (40 to 60 mg/mL) are palmitic acid and the activity of lipase content in Bacillus megaterium growth medium are equivalent to 24.60 mg/mL concentration of enzyme tablet solution; shown by the change of palmitic acid concentration which have the linearity of R = 0.97.